Genes for wheat stem rust resistance postulated in German cultivars and their efficacy in seedling and adult‐plant field tests. (30th April 2018) - Flath, Kerstin; Miedaner, Thomas; Olivera, Pablo D.; Rouse, Matthew N.; Jin, Yue
Abstract: Stem rust of wheat (caused by Puccinia graminis f.sp. tritici ) gained high international attention in the last two decades, but does not occur regularly in Germany. Motivated by a regional epidemic in 2013, we analysed 15 spring and 82 winter wheat cultivars registered in Germany for their resistance to stem rust at the seedling stage and tested 79 of these winter wheat cultivars at the adult‐plant stage. A total of five seedling stem rust resistance genes were postulated: Sr38 occurred most frequently ( n  = 29), followed by Sr31 ( n  = 11) and Sr24 ( n  = 8). Sr7a and Sr8a occurred only in two spring wheat genotypes each. Four cultivars had effective seedling resistance to all races evaluated that could only be explained by postulating additional resistance genes ('Hyland', 'Pilgrim PZO', 'Tybalt') or unidentified gene(s) ('Memory'). The three winter wheat cultivars ('Hyland' 'Memory' and 'Pilgrim PZO') were also highly resistant at the adult‐plant stage; 'Tybalt' was not tested. Resistance genes Sr24 and Sr31 highly protected winter wheat cultivars from stem rust at the adult‐plant stage in the field. Disease responses of cultivars carrying Sr38 varied. Mean field stem rust severity of cultivars without postulated seedling resistance genes ranged from 2.71% to 41.51%, nine of which were significantly less diseased than the most susceptible cultivar. This suggests adult‐plant resistance to stem rust may be present in German wheat cultivars.